Membangun Konsepsi Perburuhan Islam Di Indonesia - Abidin, Sahal, Prof . Dr. Harun, SH,M,Hum, Wardah Yuspin, S.H.,M.Kn.,Ph.D (2017)
The employment relationship formulated by positive law is felt to be unable to address the problems of labor in Indonesia. For that new formula is needed as part of efforts to reconstruct labor law in Indonesia. The concept offered by Islam is expected to be a solution in overcoming the dynamics of labor in Indonesia. The research method used in this research is a comparative normative juridical research method. The study focused on the comparison between patterns of employment relations established by positive law and the pattern of employment relationships offered by the Islamic Concept. The concept of employment formulated by Islam as a pattern of management behavior based on the respect of each individual as potential, capability, experience, in realizing the fulfillment of the rights and obligations of workers and employers. Keywords: islam, positive law, concept, labor.